Peran Intelijen Perpajakan dalam Meningkatkan Penerimaan Pajak - Aditya Kusuma, I Gusti Putu; Fredy Maradona, Agus (E-Jurnal Akuntansi, 2020)
This study aims to explore the role of the tax intelligence unit in increasing tax revenues in Indonesia. This study employs a qualitative approach, particularly the case study method, using the Bali Regional Tax Office as a research setting. Through in-depth interviews and a data analysis that comprises of data condensation, data display, and conclusion drawing and verification, this study shows that the tax intelligence unit performs effectively in boosting tax revenues through three main steps: investigation, security, and accumulation. The findings of this study present substantial implications to the Indonesian tax authority in strengthening its tax intelligence and maximizing the tax revenues. Keywords: Tax; Tax Intelligence Unit; Investigation; Security; Accumulation.